2020
DOI: 10.1177/1945892420961969
|View full text |Cite
|
Sign up to set email alerts
|

Dupilumab as Add-on Therapy for Chronic Rhinosinusitis With Nasal Polyposis in Aspirin Exacerbated Respiratory Disease

Abstract: Background Aspirin-exacerbated respiratory disease (AERD) affects 7% of asthmatics. Usual therapies are inadequate for asthma and/or nasal polyposis, leading to decreased quality of life. Objective Our objective was to evaluate the efficacy of dupilumab in AERD patients with uncontrolled, chronic rhinosinusitis with nasal polyposis (CRSwNP). Methods Patients 18 years and older with a physician diagnosis of AERD and sino-nasal outcome test 22 (SNOT 22) score ≥19 despite standard medical therapy were eligible fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 35 publications
1
33
0
1
Order By: Relevance
“…53 In 2020, Mustafa et al followed 10 patients with AERD treated with placebo for 1 month, followed by dupilumab as add-on therapy for 6 months. 19 In addition to improved SNOT-22 and Lund-MacKay computed tomography scores, most patients also had improved tolerance to alcohol, a result which was reproduced in a separate case series. 54 While omalizumab (anti-IgE) has been approved by the FDA for asthma and idiopathic urticaria since 2003, in December 2020, it joined dupilumab as the only other FDA-approved biologic for nasal polyps.…”
Section: Medical Management: Biologicsmentioning
confidence: 68%
See 1 more Smart Citation
“…53 In 2020, Mustafa et al followed 10 patients with AERD treated with placebo for 1 month, followed by dupilumab as add-on therapy for 6 months. 19 In addition to improved SNOT-22 and Lund-MacKay computed tomography scores, most patients also had improved tolerance to alcohol, a result which was reproduced in a separate case series. 54 While omalizumab (anti-IgE) has been approved by the FDA for asthma and idiopathic urticaria since 2003, in December 2020, it joined dupilumab as the only other FDA-approved biologic for nasal polyps.…”
Section: Medical Management: Biologicsmentioning
confidence: 68%
“…Importantly, patients often tolerate alcohol after aspirin desensitization or dupilumab therapy. 18,19 This unique aspect of therapy may be a motivating factor for some patients to undergo these treatments.…”
Section: Diagnosismentioning
confidence: 99%
“…Ten patients were treated for 6 months and showed improvement in both SNOT and asthma measures. 9 Several case reports and case series have also shown effectiveness of dupilumab for the treatment of PN. One study found that dupilumab treatment led to a reduction of the Numeric Rating Scale Itch Intensity to 0 in 4 patients with recalcitrant PN.…”
Section: Discussionmentioning
confidence: 99%
“…Because type 2 biomarkers such as IgE, IL-5, IL-4, and IL-13 play a critical role in the asthma and CRSwNP pathogenesis, the use of new biologics (dupilumab, omalizumab, mepolizumab, benralizumab) inhibiting these type 2 targets represents a new rational approach. Some of these biologics have recently shown induction of NSAID tolerance (omalizumab) 9 and reduction of biosynthesis of CysLTs monitored as decreased urinary LTE 4 (omalizumab, dupilumab) 9,10 in patients with AERD. The first trials in patients with severe and uncontrolled CRSwNP are encouraging because they suggest a better response in patients with AERD.…”
Section: Therapeutic Approachmentioning
confidence: 99%